A Lyapunov-Type Inequality for a Fractional Differential Equation under a Robin Boundary Condition. (19th May 2015) - Jleli, Mohamed; Ragoub, Lakhdar; Samet, Bessem
Abstract : We establish a new Lyapunov-type inequality for a class of fractional differential equations under Robin boundary conditions. The obtained inequality is used to obtain an interval where a linear combination of certain Mittag-Leffler functions has no real zeros.